Dementia screening tools in General Practice - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionGlobal and local societies experience problem of changes in demographic structure. The demographic transformation will be associated with increasing number of health, social and economic problems. One of them is dementia, commonly diagnosed among people over 65 years of age. Screening for dementia allows earlier diagnosis and treatment of disease, providing better long-time effects. General practitioner is one of the healthcare professionals most commonly seen by patients with their everyday health problems. Thus, doctors from this branch of medicine are mostly entitled to perform screening for many diseases including dementia. There are many dementia screening tools available.ObjectiveThe objective of this work is to present dementia screening tool suitable to use in general practice environment.ResultsThe most widely used is Mini Mental State Examination test. It is used both for initial assessment and for tracking the dynamics of changes over time. Other test as Montreal Cognitive Assessments test or Clock Drawing Test, Short Test of Mental Status are screening tools for detecting mild cognitive impairment. In general practices some other tools as GPCOG, Mini-Cog and MIS can be used. They are recommended due to simplicity of performance and short time required to perform examination.ConclusionsMany tests are recently developed to perform screening for dementia. In general practice environment only tests with high reliability and short time of performance can be implemented. MMSE is the most widely used questionnaire in clinical setting. Apart from this tool, it is suggested to use GPCOG, Mini-Cog, MIS as time of their application is highly adjusted to conditions of general practice and have high sensitivity and specificity.